Application of CRISPR/Cas9 System for Plasmid Elimination and Bacterial Killing of Bacillus cereus Group Strains - Wang, Xiaojing; Lyu, Yufei; Wang, Siya; Zheng, Qingfang; Feng, Erling; Zhu, Li; Pan, Chao; Wang, Shenghou; Wang, Dongshu; Liu, Xiankai; Wang, Hengliang (Frontiers in Microbiology, 2021)
The CRISPR-Cas system has been widely applied in prokaryotic genome editing with its high efficiency and easy operation. We constructed some “scissors plasmids” via using the temperature-sensitive pJOE8999 shuttle plasmid, which carry the different 20nt (N20) guiding the Cas9 nuclease as a scissors to break the target DNA. We successfully used scissors plasmids to eliminate native plasmids from Bacillus anthracis and B. cereus, and specifically killed B. anthracis. When curing pXO1 and pXO2 virulence plasmids from B. anthracis A16PI2 and A16Q1, respectively, we found that the plasmid elimination percentage was slightly higher when the sgRNA targeted the replication initiation region (96%–100%), rather than the non-replication initiation region (88%–92%). We also tried using a mixture of two scissors plasmids to simultaneously eliminate pXO1 and pXO2 plasmids from B. anthracis, and the single and double plasmid-cured rates were 29% and 14%, respectively. To our surprise, when we used the scissor plasmid containing two tandem sgRNAs to cure the target plasmids pXO1 and pXO2 from wild strain B. anthracis A16 simultaneously, only the second sgRNA could guide Cas9 to cleave the target plasmid with high efficiency, while the first sgRNA didn’t work in all the experiments we designed. When we used the CRISPR/cas9 system to eliminate the pCE1 mega-virulence plasmid from B. cereus BC307 by simply changing the sgRNA, we also obtained a plasmid-cured isogenic strain at a very high elimination rate (69%). The sterilization efficiency of B. anthracis was about 93%, which is similar to the efficiency of plasmid curing, and there was no significant difference in the efficiency of among the scissors plasmids containing single sgRNA, targeting multi-sites, or single-site targeting and the two tandem sgRNA. This simple and effective curing method, which is applicable to B. cereus group strains, provides a new way to study these bacteria and their virulence profiles.